Effect of forum selection clauses in investment arbitration [Articol] - Dolea, Sorin (CEP USM, 2019)
The conclusion of contracts between investors and host States is a common feature in international investment law. In many disputes, such investment agreements play a major role. The existence of such contractual agreements and the claims arising in the investment disputes surrounding them, have given rise to a plethora of legal issues, which will be addressed in this contribution. Initially, it is necessary to distinguish between breaches of a treaty and breaches of contract. Not every breach of a contract by a State amounts to a breach of international law. There is a large body of case law setting out the line at which a breach of contract under domestic law amounts also to a breach of international law. This can either be due to the specific circumstances of the breach or to the existence of an umbrella clause. Cases involving breaches of contract invariably also have given rise to complex disputes about the jurisdiction of the treaty-based tribunal deciding on them. The main questions have focused on whether such tribunals can hear claims based on the breach of a contract as a preliminary question to determining a breach of a treaty, the jurisdiction of treaty-based tribunals to hear claims for the breach of contracts not amounting to breaches of international law and the relevance of contractually agreed dispute resolution provisions. None of the above questions have yet produced uniform answers. There are, however, certain approaches depending whether the applicable investment treaty provide for an “umbrella clause”, or the investment treaty has a limited rationae materie scope of protection. These aspects will be discussed in this article.

Încheierea contractelor între investitorii străini și statele-gazdă este o practică comună a dreptului internațional al investițiilor. Existența raporturilor contractuale în disputele investiționale au dat naștere la o mulțime de probleme juridice, care vor fi abordate în acest articol. Inițial, este necesar să se facă distincția dintre încălcarea unei obligații prevăzute de un tratat investițional și încălcarea obligațiilor contractuale încheiate între investitorul străin şi statul-gazdă. Nu orice încălcare a unui contract de către un stat reprezintă o încălcare a dreptului internațional. O parte din jurisprudența investițională stabilește abordarea, conform căreia o încălcare a contractului în conformitate cu legislația internă echivalează cu o încălcare a dreptului internațional. Acest lucru poate fi cauzat fie de circumstanțele specifice ale încălcării, fie de existența unei clauze umbrelă. Cazurile care implică încălcări ale contractului au generat, de asemenea, invariabil dispute complexe cu privire la competența tribunalului bazat pe un tratat investițional care decide asupra unei pretenții contractuale. Principalele probleme sunt dacă aceste tribunale pot examina cereri bazate pe încălcarea unui contract ca o problemă preliminară pentru determinarea încălcării obligațiilor ce reies dintr-un tratat investițional, competenței tribunalelor bazate pe tratate de a soluționa pretențiile contractuale care nu constituie încălcări ale dreptului internațional și aplicabilităţii clauzei de selecție a forului în materie de soluționare a litigiilor contractuale. Niciuneia dintre întrebările de mai sus nu i s-au dat deocamdată răspunsuri uniforme. Există, totuși, anumite abordări care depind de faptul dacă tratatul investițional aplicabil prevede o „clauză umbrelă” sau dacă scopul de protecție ratione materiae a tratatului prevede anumite limitări. Aceste aspecte vor fi discutate in articol.
EFECTUL CLAUZEI DE SELECȚIE A FORULUI ÎN ARBITRAJUL INVESTIŢIONAL
Keywords: investment protection; contract claims; observance of investment undertakings; investment arbitration; scope of protection; protejarea investițiilor; pretenții contractuale; respectarea angajamentelor investiționale